Human Engineered Heart Tissue Patches Remuscularize the Injured Heart in a Dose-Dependent Manner. Issue 20 (18th May 2021) - Querdel, Eva; Reinsch, Marina; Castro, Liesa; Köse, Deniz; Bähr, Andrea; Reich, Svenja; Geertz, Birgit; Ulmer, Bärbel; Schulze, Mirja; Lemoine, Marc D.; Krause, Tobias; Lemme, Marta; et al.
Abstract : Background: Human engineered heart tissue (EHT) transplantation represents a potential regenerative strategy for patients with heart failure and has been successful in preclinical models. Clinical application requires upscaling, adaptation to good manufacturing practices, and determination of the effective dose. Methods: Cardiomyocytes were differentiated from 3 different human induced pluripotent stem cell lines including one reprogrammed under good manufacturing practice conditions. Protocols for human induced pluripotent stem cell expansion, cardiomyocyte differentiation, and EHT generation were adapted to substances available in good manufacturing practice quality. EHT geometry was modified to generate patches suitable for transplantation in a small-animal model and perspectively humans. Repair efficacy was evaluated at 3 doses in a cryo-injury guinea pig model. Human-scale patches were epicardially transplanted onto healthy hearts in pigs to assess technical feasibility. Results: We created mesh-structured tissue patches for transplantation in guinea pigs (1.5×2.5 cm, 9–15×10 6 cardiomyocytes) and pigs (5×7 cm, 450×10 6 cardiomyocytes). EHT patches coherently beat in culture and developed high force (mean 4.6 mN). Cardiomyocytes matured, aligned along the force lines, and demonstrated advanced sarcomeric structure and action potential characteristics closely resembling human ventricular tissue. EHT patches containing ≈4.5, 8.5, 12×10 6, or no cells were transplanted 7 days after cryo-injury (n=18–19 per group). EHT transplantation resulted in a dose-dependent remuscularization (graft size: 0%–12% of the scar). Only high-dose patches improved left ventricular function (+8% absolute, +24% relative increase). The grafts showed time-dependent cardiomyocyte proliferation. Although standard EHT patches did not withstand transplantation in pigs, the human-scale patch enabled successful patch transplantation. Conclusions: EHT patch transplantation resulted in a partial remuscularization of the injured heart and improved left ventricular function in a dose-dependent manner in a guinea pig injury model. Human-scale patches were successfully transplanted in pigs in a proof-of-principle study. Abstract : Supplemental Digital Content is available in the text.